The riddle of Hume's Treatise : skepticism, naturalism, and irreligion - Russell, Paul, 1955- (Oxford : Oxford University Press, 2008)
It is widely held that Hume's Treatise has little or nothing to do with problems of religion. Contrary to this view, Paul Russell argues that it is irreligious aims and objectives that are fundamental to the Treatise and account for its underlying unity and coherence.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Hume, David, -- 1711-1776.; Religion -- Philosophy